An empirical study of the relationship between performance based pay and job satisfaction - Azman, Ismail; Hasan Al-Banna, Mohamed; Mohd Hamran, Mohamad; Eveleena Afzan, Hassan; Nurzawani, Zakaria (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.